Utilization of Plants as Natural Dyes in Batik Incung of the Kerinci Community, Jambi Province, Indonesia - Tiara Tiara; Hendra Lardiman; Sari Anggraini (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2025)
Background: Batik Incung, a specialty in Sungai Penuh City, is a unique product that incorporates historical Kerinci tribe motifs, flora, and fauna. The use of plants as natural dyes enhances the value of the batik. Methodology: This ethnobotanical research employs an exploratory approach and was conducted in three central villages of Incung batik production, namely Sungai Penuh, Simpang Tiga Rawang, and Penawar Village. Data were collected through interviews with four Incung Batik artisans, compleneted by field surveys and direct observations to identify the plants used as dyes. Findings: The results showed that there were 14 species of plants used by Incung Batik artisans. The plant parts used were leaves, stem bark, seeds, roots, rhizomes, fruits, and fruit peels. These plants were obtained through cultivation, either from the wild or purchased in the market. Contribution: This research documents and enriches ethnobotanical data to support the preservation of local biodiversity, particularly within the Incung batik industry. Consequently, it promotes the development of innovative batik industry grounded in local wisdom, sustainability, and eco-friendliness